Examining the leadership styles among High School teachers at Dominican schools in Indonesia - Agus Hermawan (International Journal of Humanities and Innovation (IJHI), 2021)
Spiritual leadership in the education field is not something new. However, it has not been deeply examined. Studies on spiritual leadership are more easily found in the non-educational than in educational fields (Scott & Tweed, 2016). For that reason, drawing on spiritual leadership and Dominican spirituality, the researcher examined how Dominican Schools in Indonesia integrate Dominican spirituality and leadership in their teaching performances. A leadership styles (Lewin’s leadership styles) questionnaire and collaborative leadership survey through Google form was conducted to collect data from 114 high school teachers of six Dominican Schools in Indonesia. The study results were a) Dominican spirituality provides unity of leadership styles among the high school teachers at Dominical Schools, b) leadership styles adopted by teachers are in line with Dominican spirituality leadership. Therefore, a positive correlation between Dominican spirituality and educational leadership was rooted in the values and vision of Dominican Educational Institution and became an educational leadership identity among high school teachers. The researcher suggests that curriculum designers and education facilitators collaborate to include and practice Dominican spiritual leadership as one of the principles and visions in Dominican educational institutions. It can also be used to describe other institutions with similar charisms. This study also advises that future researchers perform a poll on "Dominican Spiritual Leadership" using quantitative research methodologies. It is necessary to investigate the relationship between Dominican spiritual leadership and other educational characteristics in-depth. Educational levels, teaching experience, gender, community culture, and other factors may influence stakeholders in Dominican schools and other educational institutions worldwide.